Diagnosis and treatment of volvulus of the sigmoid colon - Estapé, Gonzalo; Viola Núñez, Humberto (Cirugía del Uruguay, 1973)
Sigmoid volvulus is rare and extremely serious; the author presents 7 cases with corresponding documentation and discusses diagnosis and therapy.